Striped patterns for generalized antiferromagnetic functionals with power law kernels of exponent smaller than d+2. (March 2022) - Kerschbaum, Alicja
Abstract: We consider a class of continuous generalized antiferromagnetic models with local/nonlocal interactions. The functional consists of an anisotropic perimeter term and a repulsive nonlocal term with a power law kernel. In certain regimes the two terms enter in competition and symmetry breaking with formation of periodic striped patterns is expected to occur. In this paper we extend some recent results of Daneri and Runa to power law kernels within a range of exponents smaller than d + 2 and strictly larger than d + 1, being d the dimension of the underlying space. In particular, we prove that in a suitable regime minimizers are periodic unions of stripes with a given optimal period. Notice that the exponent d + 1 corresponds to an anisotropic version of the model for pattern formation in thin magnetic films.